2016
DOI: 10.1080/09168451.2015.1072463
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic synthesis of 3,4,5,3′,5′-pentahydroxy-trans-stilbene from piceatannol by two-component flavin-dependent monooxygenase HpaBC

Abstract: HpaBC monooxygenase was previously reported to hydroxylate resveratrol to piceatannol. In this article, we report a novel catalytic activity of HpaBC for the synthesis of a pentahydroxylated stilbene. When Escherichia coli cells expressing HpaBC were incubated with resveratrol, the resulting piceatannol was further converted to a new product. This product was identified by mass spectrometry and NMR spectroscopy as a 5-hydroxylated piceatannol, 3,4,5,3',5'-pentahydroxy-trans-stilbene (PHS), which is a reportedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…The corresponding aglycon, piceatannol (2b), was synthesized from resveratrol (4b) by biochemical hydroxylation at the C-3′ position (Scheme 3). 37,38) The partially acetylated form 2c was also prepared from 4c by chemical oxidation. 39) In the latter case with 2-iodoxybenzoic acid (IBX)mediated oxidation, a free hydroxy group at C-4′ is necessary, and others at C-3 and C-5 should be protected.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding aglycon, piceatannol (2b), was synthesized from resveratrol (4b) by biochemical hydroxylation at the C-3′ position (Scheme 3). 37,38) The partially acetylated form 2c was also prepared from 4c by chemical oxidation. 39) In the latter case with 2-iodoxybenzoic acid (IBX)mediated oxidation, a free hydroxy group at C-4′ is necessary, and others at C-3 and C-5 should be protected.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme complex HpaBC generally has a great demand for oxygen in the hydroxylation reaction [ 20 ]. However, we found that eriodictyol production was not linearly correlated with the culture volume, which is an indirect measure of oxygen supply.…”
Section: Discussionmentioning
confidence: 99%
“…Kino et al have demonstrated that two-component FMO HpaBC could not only selectively hydroxylate chemically-complex resveratrol, [185] but also the hydroxylated-product, piceatannol. [186] The latter reaction afford 3,4,5,3',5'-pentahydroxy-trans-stilbene (PHS), a biologically-active stilbene derivative in 1.8 g L À 1 product titre, and represented the first example of this enzymatic hydroxylation. [186] Hong et al also studied the regioselective hydroxylation of stilbene compounds but with a different FMO, Sam5.…”
Section: Late-stage Functionalisationmentioning
confidence: 99%
“…[186] The latter reaction afford 3,4,5,3',5'-pentahydroxy-trans-stilbene (PHS), a biologically-active stilbene derivative in 1.8 g L À 1 product titre, and represented the first example of this enzymatic hydroxylation. [186] Hong et al also studied the regioselective hydroxylation of stilbene compounds but with a different FMO, Sam5. [187] The group studied Sam5 3'-hydroxylase activities on a series of methylated-resveratrol analogues (pinostilbene and pterostilbene) and hydroxylated-resveratrol (oxyresveratrol), which produced the 3'-hydroxylated products in 37-54 % conversions.…”
Section: Late-stage Functionalisationmentioning
confidence: 99%